A coordenação pedagógica e o professor articulador de aprendizagem : a dialogicidade em torno da prática educativa - Souza, Márcia Inês de (2021)
This research presents studies on the educational process in basic education, establishing dialogic connections with professionals who work in specific functions at school: Pedagogical Coordination and Learning Articulator Teacher. The study of relationships in this context was motivated during my professional formation, by the particularities of the functions, and became my research object at the master's degree linked to the Postgraduate Program in Education (PPGEdu/UFR-MT) of the Teacher Training and Educational Public Policies and was designed from the research question: How is the dialogic relationship established between the Pedagogical Coordination and the Learning Articulator Teacher in the school context? Thus, the research is based on Freire's theoretical assumption to reflect on dialogicity and coordination as a dialogical praxis. The general objective of the research was defined as investigating the dialogicity in educational practice at school involving the Pedagogical Coordination and the Learning Articulator Teacher. For that, some specific objectives were listed, namely: understand how the Pedagogical Coordination develops the pedagogical action with the Learning Articulator Teacher; reflect on the Pedagogical Coordination function in the daily school’s life, considering the numerous aspects that involve it; analyze the limits and possibilities of dialogicity as an instrument of mediation in educational practice; characterize the contributions of the work of the Learning Articulator Teacher in the pedagogical practice. The option for the Freirian dialectical-dialogical method, to understand the relationships established between the subject, the social context, the pedagogical practice and the organizational situation of the institution and the policies that govern school education was based on the perspective of qualitative analysis, where the dialogue characterizes itself in an orientation axis in the construction of meanings. For the empirical construction an analysis of the Pedagogical Political Project (PPP) was performed of each school involved in the research, the legal documents of the State Department of Education (SEDUC/MT) that order the functions in the context of the school organized by Cycles, and still, through a questionnaire and semi-structured interview, a data survey was carried out with 3 coordinators and 3 articulator teachers from three schools of basic education on the network of Mato Grosso’s state. Data analysis provided a broader understanding of how the pedagogical coordination develops the action with the articulator teacher and showed that there are important movements for dialogue between them. The limits and possibilities of dialogicity at school were reflected in the data analysis. In the school context, there are many possibilities of the dialogical relationship, the participants are unanimous in reporting its importance for the good development of the practice, for improving the pedagogical process in general at school and for strengthening the pedagogical action developed by the Articulator Teacher. The limits of dialogicity reflected in the research data demonstrate the situations that do not collaborate to dialogic interactions, the daily dynamics, as well as official guidelines are pointed out as hindering the dialogue between the actors in the pedagogical process. Regarding the potential of the function in the school context, the Articulator Teacher can build, together with the coordinator, dialogical relationships that involve all the teachers and the dialogue proves to be very successful for student learning. I add another important aspect, that if the Articulator Teacher is given an opening to work in collaboration with all the teachers, he will contribute to improve the pedagogical process in the school. The research also showed that all actions matter, whether in the classroom, in pedagogical meetings, in training spaces, in social movements, in a study group, regardless of function, critical analysis directs to strengthen the teacher's action at school.